Language, cognition, and human nature selected articles - Pinker, Steven 1954- (Oxford, United Kingdom Oxford University Press, 2013)
Pinker's seminal research explores the workings of language and its connections to cognition, perception, social relationships, child development, human evolution, and theories of human nature. This eclectic collection spans Pinker's thirty-year career, exploring his favorite themes in greater depth and scientific detail. It includes thirteen of Pinker's classic articles, ranging over topics such as language development in children, mental imagery, the recognition of shapes, the computational architecture of the mind, the meaning and uses of verbs, the evolution of language and cognition, the nature-nurture debate, and the logic of innuendo and euphemism. Each outlines a major theory or takes up an argument with another prominent scholar, such as Stephen Jay Gould, Noam Chomsky, or Richard Dawkins.
Formal models of language learning -- A computational theory of the mental imagery medium -- Rules and connections in human language / with Alan Prince -- When does human object recognition use a viewer-centered reference frame? / with Michael Tarr -- Natural language and natural selection / with Paul Bloom -- The acquisition of argument structure -- The nature of human concepts : evidence from an unusual source / with Alan Prince -- Why nature and nurture won't go away -- The faculty of language : what's special about it? / with Ray Jackendoff -- So how does the mind work? -- Deep commonalities between life and mind -- Rationales for indirect speech : the theory of the strategic speaker / with James Lee -- The cognitive niche : coevolution of intelligence, sociality, and language.
Includes bibliographical references and index.
Keywords: Language acquisition; Cognition; Psycholinguistics